A Musicology of Performance Theory and Method Based on Bach's Solos for Violin - Fabian, Dorottya (Open Book Publishers, 2015)
"This book examines the nature of musical performance. In it, Dorottya Fabian explores the contributions and limitations of some of these approaches to performance, be they theoretical, cultural, historical, perceptual, or analytical. Through a detailed investigation of recent recordings of J. S. Bach's Six Sonatas and Partitas for Solo Violin, she demonstrates that music performance functions as a complex dynamical system. Only by crossing disciplinary boundaries, therefore, can we put the aural experience into words. A Musicology of Performance provides a model for such a method by adopting Deleuzian concepts and various empirical and interdisciplinary procedures. Fabian provides a case study in the repertoire, while presenting new insights into the state of baroque performance practice at the turn of the twenty-first century. Through its wealth of audio examples, tables, and graphs, the book offers both a sensory and a scholarly account of musical performance. These interactive elements map the connections between historically informed and mainstream performance styles, considering them in relation to broader cultural trends, violin schools, and individual artistic trajectories. A Musicology of Performance is a must read for academics and post-graduate students and an essential reference point for the study of music performance, the early music movement, and Bach's opus."